More rapid polar ozone depletion through the reaction of HOCI with HCI on polar stratospheric clouds - Prather, MJ (Nature, 1992)
THE direct reaction of HOC1 with HC1, known to occur in liquid water1and on glass surfaces2, has now been measured on surfaces similar to polar stratospheric clouds3,4and is shown here to play a critical part in polar ozone loss. Two keys to understanding the chemistry of the Antarctic ozone hole5-7are, one, the recognition that reactions on polar stratospheric clouds transform HC1 into more reactive species denoted by ClOx(refs 812) and, two, the discovery of the ClO-dimer (C12O2) mechanism that rapidly catalyses destruction of O3(refs 1315). Observations of high levels of OClO and ClO in the springtime Antarctic stratosphere1619confirm that most of the available chlorine is in the form of ClOx(refs 20, 21). But current photochemical models22,23have difficulty converting HC1 to ClOxrapidly enough in early spring to account fully for the observations5-7,20,21. Here I show, using a chemical model, that the direct reaction of HOC1 with HC1 provides the missing mechanism. As alternative sources of nitrogen-containing oxidants, such as N2O5and ClONO2, have been converted in the late autumn to inactive HNO3by known reactions on the sulphate-layer aerosols24-27, the reaction of HOC1 with HC1 on polar stratospheric clouds becomes the most important pathway for releasing that stratospheric chlorine which goes into polar night as HC1. © 1992 Nature Publishing Group.